ANOMALI Anomali Bouguer Lengkap Untuk Mengidentifikasi Sistem Panas Bumi Gunung Pandan Jawa Timur - Irma Risvana Dewi; Dara Puspita Anggraeni; Dwi Kartika Risfianty; Irna Il Sanuriza (Fakultas MIPA Universitas Nahdlatul Wathan Mataram, 2022)
The world population is predicted to continue increasing. Therefore, discovering another energy resource instead of fossil oil is essential. The geothermal resource can be used as alternative renewable energy. To identify the complex geothermal system in East Java as alternative renewable energy based on the gravity anomaly. This research investigated the Gunung Pandan geothermal system. The geophysical method was used which is the gravity method. The subsurface information was investigated using the Bouger Gravity Anomaly (ABL) method. The results show that the distribution of the gravitational anomaly in the Mount Pandan complex has a residual anomaly value of -3.2 mgal to 11.7 mgal. The residual anomalous contours represent positive clusters identified as intrusive rocks that heated the fluid around the fault and the suspected reservoir. thus, forming the manifestation of Banyukuning and Selogajah with the flow zone of each manifestation classified as an outflow zone for the manifestation of Banyukuning and upflow for the manifestation of Selogajah.